OtoSeq Next‐Generation DNA Sequencing in the Evaluation of Congenital Sensorineural Hearing Loss. (2nd September 2014) - Goico, Brian; Holle, Jennifer; Manickam, Vi; Johnson, Judith; Sivakumaran, Theru A; Zhang, Kejian; Greinwald, John H.
Abstract : Objectives: Congenital sensorineural hearing loss (SNHL) is relatively common, occurring in 2 to 4 per 1000 infants, with genetic etiologies accounting for nearly 67% of cases. The clinical presentation of patients with syndromic and nonsyndromic SNHL is often indistinguishable. Establishing specific genetic causes is imperative for clinical management and genetic counseling. Recent advances in next‐generation sequencing have allowed for facilitated multi‐gene testing in genetically heterogeneous conditions such as SNHL. The present study evaluates the clinical utility of one such assay, OtoSeq, in genotyping pediatric patients with SNHL. Methods: Demographic, audiometric, imaging, and genetic data were retrospectively collected from 70 patients with prelingual hearing loss who underwent clinical genetic testing of 23 well‐studied SNHL genes via OtoSeq, our next generation sequencing platform. The frequencies of pathogenic and likely pathogenic mutations were calculated and audiogram data were reviewed. Results: Of 70 patients studied, 15 patients (21%) were found to have an identifiable genetic etiology for their hearing loss, and 8 patients were found to have a previously undiagnosed genetic syndrome. Seven patients were diagnosed with nonsyndromic hearing loss. A total of 27 patients with mutations had adequate audiogram data available, of which 16 had mild to moderate hearing loss (59.3%) and 11 had severe to profound hearing loss (40.7%). Several unique combinations of deafness causing mutations in different genes were identified, including CDH23 and MYO7A, both Usher pathway of genes. Conclusions: This study demonstrates that OtoSeq is a valuable tool for determining genetic causes of SNHL in pediatric patients, which has direct implications for their clinical management.